The Development of Innovative Design Competency according to the Design Thinking Concept for the Graduates in Special Education Program - Tasaboomrung, Nampech; Songserm, Ubonwan (Journal Of Ratchasuda Institute for Research and Development of Persons With Disabilities, 2023)
This research was the development of innovative design competency according to the design thinking concept for the graduates in Special Education program. The objectives of the study were: (1) to develop the innovative design competency according to the design thinking concept for the graduates in Special Education program, (2) to study the satisfaction of the graduates in Special Education program who were taught by the teaching method according to the design thinking concept. The samplings were 9 graduates who were studying in Special Education program. They were selected from the purposive sampling. The research method was the quasi-experimental design, and the one group pretest-posttest design was used in this study. The findings were as follows: (1) According to the result of the development of innovative design competency according to the design thinking concept for the graduates in Special Education program, the mean score was 88.15 percentage. This result passed the criteria related to the hypotheses. (2) The results of the satisfaction of the graduates who were studying in Special Education program were divided into 3 parts. The first part was the instruction. The mean score was 4.51 and the standard deviation was 0.55. The satisfaction was in the highest level. The second part was the instructional media. The mean score was 4.50 and the standard deviation was 0.51. The satisfaction was in the highest level. The third part was the assessment and evaluation. The mean score was 4.56 and the standard deviation was 0.56. The satisfaction was in the high level. Moreover, the mean score of all parts was 4.50 and the standard deviation was 0.51. The satisfaction was in the highest level. Consequently, the research results passed the criteria according to the hypotheses.